Inside Cover. Issue 12 (22nd December 2020) - Milanesi, Alessio; Magni, Giada; Centi, Sonia; Schifino, Gioacchino; Aluigi, Annalisa; Khlebtsov, Boris N.; Cavigli, Lucia; Barucci, Andrea; Khlebtsov, Nikolai G.; Ratto, Fulvio; Rossi, Francesca; Pini, Roberto
Abstract: Cross‐polarised optical coherence tomography is a promising technique to reveal certain pathologic conditions in tissue. However, endoscopic devices with flexible small probes to detect diseased areas intraoperatively barely exist. We present an extension of a commercially available swept‐source OCT system. Applying a common‐path probe, the polarisation of reference and sample arm does not need to be further balanced. Due to a depolariser, the system is independent of the inputpolarisation. Further details can be found in the article by Katharina Blessing, Judith Schirmer, Gargi Sharma, and Kanwarpal Singh. (e202000135 ). Abstract : Vascular disrupting agents (VDAs) can be used to damage the tumour vasculature, suppressing oxygen and nutrition supply to the tumour tissue. Photoacoustic imaging was used to assess the structural and functional changes of the tumour vasculature and evaluate the efficacy of the VDAs. Tissues are irradiated with short laser pulses and the photoacoustic waves are analyzed to extract vessel size and hemoglobin composition to evaluate the VDA, hours after administration. Further details can be found in the article by Muhannad N Fadhel, Sila Appak Baskoy, Yanjie Wang, Eno Hysi, and Michael C. Kolios (e202000209 ).